POLICE COMPLIANCE WITH HUMAN RIGHTS STANDARDS DURING ARREST AND DETENTION IN ABUJA, NIGERIA - Ivoke, Paul Agwu; Yankuzo, Kabiru Ibrahim (African Journal of Social and Behavioural Sciences, 2025)
Despite constitutional protections under Section 35 of the 1999 Constitution and the Administration of Criminal Justice Act (ACJA) 2015, human rights violations remain pervasive within the Nigerian Police Force (NPF) during arrest and detention in Abuja. Guided by Conflict Theory, this cross-sectional survey engaged 397 respondents to assess compliance, barriers, and impacts on public trust. Findings indicate inconsistent adherence to rights standards: suspects frequently experienced torture, denial of legal counsel, delayed court presentations, and arrests without warrants, while treatment of female detainees and human rights training showed comparatively better, yet uneven, compliance. Institutional and operational barriers—including corruption, inadequate funding, weak internal discipline, political interference, and outdated practices—alongside societal tolerance of police brutality, reinforced these violations. Direct exposure to arrest and higher educational attainment were associated with more negative perceptions of compliance. These abuses eroded public trust, reduced community cooperation, and fostered fear, illustrating the systemic reproduction of power inequalities central to Conflict Theory. Respondents strongly endorsed multi-dimensional reforms, prioritizing compulsory human rights training, independent oversight of detention practices, sanctions for offending officers, enhanced funding, and public awareness campaigns. The study recommends immediate interventions focusing on training and accountability mechanisms, alongside long-term reforms encompassing institutional restructuring and strengthened legal enforcement, to restore citizens’ rights, confidence, and trust in policing.